SIMULASI PENJALARAN GELOMBANG P-SV 2D DENGAN METODE FINITE DIFFERENCE MENGGUNAKAN GRAPHICS PROCESSING UNIT, STUDI KASUS SIMULASI SEISMIK REFLEKSI PADA MODEL MARMOUSSI2 - , LEO CAHYA DINENDRA, Sudarmaji, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Numerical modelling of P-SV wave propagation has been made using finite difference staggered-grid method in CUDA C. To accelerate numerical computation when running on very large size of model, program modified in CUDA C which paralellize the computation using GPU. This program has been verified by comparison between numerical seismogram and analytic curve of travel-time that obtained by calculation of two layer medium using Snellâs Law. This comparison shows the suitability between travel times of direct, reflected, and converted wave and the analytical curve, even though the refracted wave cannot be compared due to difference of amplitude value from direct wave. Difference of processing time using CPU and GPU is calculated on a homogen model. The result shows that using GPU could increase the speed of calculation time up to 107 times. This program then is used to simulate an 2D seismic survey using Marmoussi2 model to get the snapshot result and syntethic seismic data. The part of Marmoussi2 model that has been used is consist of 4800à´¨2400 grids or 11,520,000 elements, with 176 times shot (30.000 iterations each shot) and sampling time 0.00176 s on CPU Core i7-2600K 3.40GHz (32 GB memory) and GPU NVIDIA GeForce GTX 590 (1.5 GB memory), this program needs at least 57.1 hours to complete the calculation